Challenges and Frugal Remedies for Lowering Facility Based Neonatal Mortality and Morbidity: A Comparative Study - Hippolite O. Amadi; Akin O. Osibogun; Olateju Eyinade; Mohammed B. Kawuwa; Angela C. Uwakwem; Maryann U. Ibekwe; Peter Alabi; Chinyere Ezeaka; Dada G. Eleshin; Mike O. Ibadin (International Journal of Pediatrics)
Millennium development goal target on infant mortality (MDG4) by 2015 would not be realised in some low-resource countries. This was in part due to unsustainable high-tech ideas that have been poorly executed. Prudent but high impact techniques could have been synthesised in these countries. A collaborative outreach was initiated to devise frugal measures that could reduce neonatal deaths in Nigeria. Prevailing issues of concern that could militate against neonatal survival within care centres were identified and remedies were proffered. These included application of (i) recycled incubator technology (RIT) as a measure of providing affordable incubator sufficiency, (ii) facility-based research groups, (iii) elective training courses for clinicians/nurses, (iv) independent local artisans on spare parts production, (v) power-banking and apnoea-monitoring schemes, and (v) 1/2 yearly failure-preventive maintenance and auditing system. Through a retrospective data analyses 4 outreach centres and one “control” were assessed. Average neonatal mortality of centres reduced from 254/1000 to 114/1000 whilst control remained at 250/1000. There was higher relative influx of incubator-dependent-neonates at outreach centres. It was found that 43% of mortality occurred within 48 hours of presentation (d48) and up to 92% of d48 were of very-low birth parameters. The RIT and associated concerns remedies have demonstrated the vital signs of efficiency that would have guaranteed MDG4 neonatal component in Nigeria.